In vitro toxicity and efficacy of verdinexor, an exportin 1 inhibitor, on opportunistic viruses affecting immunocompromised individuals. - Douglas G Widman; Savanna Gornisiewicz; Sharon Shacham; Sharon Tamir (PLoS ONE, 2018)
Infection of immunocompromised individuals with normally benign opportunistic viruses is a major health burden globally. Infections with viruses such as Epstein-Barr virus (EBV), human cytomegalovirus (HCMV), Kaposi's sarcoma virus (KSHV), adenoviruses (AdV), BK virus (BKPyV), John Cunningham virus (JCPyV), and human papillomavirus (HPV) are significant concerns for the immunocompromised, including when these viruses exist as a co-infection with human immunodeficiency virus (HIV). These viral infections are more complicated in patients with a weakened immune system, and often manifest as malignancies resulting in significant morbidity and mortality. Vaccination is not an attractive option for these immune compromised individuals due to defects in their adaptive immune response. Verdinexor is part of a novel class of small molecules known as SINE (Selective Inhibitor of Nuclear Export) compounds. These small molecules demonstrate specificity for the nuclear export protein XPO1, to which they bind and block function, resulting in sequestration of XPO1-dependent proteins in the nucleus of the cell. In antiviral screening, verdinexor demonstrated varying levels of efficacy against all of the aforementioned viruses including previously with HIV. Studies by other labs have discussed likely mechanisms of action for verdinexor (ie. XPO1-dependence) against each virus. GLP toxicology studies suggest that anti-viral activity can be achieved at a tolerable dose range, based on the safety profile of a previous phase 1 clinical trial of verdinexor in healthy human volunteers. Taken together, these results indicate verdinexor has the potential to be a broad spectrum antiviral for immunocompromised subjects for which vaccination is a poor option.